Civil Liberties and the Mentally Ill - Szasz, Thomas S. (1960)
Here are two basic ways in which a person may assume the social role of mental patient. First, it may be assumed voluntarily, meaning that the role is self-defined. Second, it may be foisted upon a person against his will. This means that a person may be defined as mentally ill by someone other than himself. This definition, then, if properly implemented, may become generally accepted or socially verified. I shall limit myself here to calling attention to certain ethical and legal aspects of the psychiatrist's involvement with the second class of mentally ill patients